Prevalence of COVID‐19 in patients with autoimmune liver disease in Europe: A patient‐oriented online survey. Issue 7 (9th June 2021) - Zecher, Britta Franziska; Buescher, Gustav; Willemse, José; Walmsley, Martine; Taylor, Alison; Leburgue, Angela; Schramm, Christoph; Lohse, Ansgar W.; Sebode, Marcial
Abstract: Background: During the current SARS‐CoV‐2 pandemic it is important to identify risk factors for COVID‐19. Registry studies are providing growing evidence on the elevated risk of mortality from COVID‐19 in patients with chronic liver disease, especially in advanced stages. Results may, however, have a selection bias towards severe cases. Limited data is available on COVID‐19 in patients with autoimmune liver disease (AILD). Aim: To perform an online survey to capture the prevalence of COVID‐19 and the state of medical care of patients with AILD in Europe during the pandemic. Methods: Data was collected via an anonymous patient‐oriented, online survey, which was available on the EUSurvey platform in nine European languages between 24 th June 2020 and 14 th October 2020. Of 1834 contributions, 51 were excluded because participants did not name an underlying AILD, and four were excluded because of duplicate data entry. Results: Of 1, 779 participants, 1, 752 resided in 20 different countries of the European Union and the United Kingdom (UK). The five countries with the highest numbers of contributions were France ( n = 450), Germany ( n = 318), the Netherlands ( n = 267), Spain ( n = 225), and the UK ( n = 183). 2.2% of participants (39/1779) had been diagnosed with COVID‐19. There were no differences regarding age, sex, AILD, the status of liver cirrhosis, or status post liver transplantation between COVID‐19 and non‐COVID‐19 cases. Of the 39 COVID‐19 cases, five patients were admitted to a regular ward, one patient was admitted to ICU and required ventilation. Conclusion: In our Europe‐wide, patient‐oriented survey on COVID‐19 in patients with AILD, we detected a low rate of COVID‐19, comparable to the period prevalence of the general population. These results suggest that patients with AILD are not at elevated risk of COVID‐19. Key Summary: Summarize the established knowledge on this subject Registry studies show that patients with advanced stages of liver disease are at risk of mortality caused by COVID‐19. But since data is entered by the treating physicians, there may be a bias towards reporting severe cases. Limited data is available on COVID‐19 in patients with autoimmune liver disease (AILD). Immunosuppressive treatment required in patients with AIH and AILD patients after liver transplantation might represent an additional risk factor. What are the significant and/or new findings of this study? In our patient‐oriented survey we did not detect a higher frequency of COVID‐19 cases in patients with AILD compared to the general population. These results suggest that patients with AILD are not at elevated risk of COVID‐19. Our study is therefore an important addition to existing registry studies evaluating the risk of COVID‐19 in patients with AILD.